Study of Supercar Community Influence on its Effect Towards Supercar Buyer's Purchase Intention - Adityawarman, Haykel; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2014)
Abstract- Having a supercar, a high-performance sports car is the dream of every car enthusiasts. But not everyone can buy supercar because of its very expensive price. Even though more people can buy a supercar nowadays, but still a lot of considerations have to be made before buying supercar because of its price. To overcome this, supercar sellers are creating a supercar community consists of supercar owners as their member. The existence of the community is advantageous for supercar seller, community can help increase the supercar’s brand image to the customer and decrease the risk that the buyer can think about. To know the buyer’s behavior in deciding to buy supercar, this research revolves in finding what factor influence the buyer’s purchase intention, and what factor that influenced by buyer’s purchase intention. Including the purchase intention itself, there are 12 variables that used in this research. The data collection method that used in this research is using questionnaire and spread to 40 supercar owners that joins supercar community in Jabodetabek area, Bandung, and Bali. After all the data collected, the data analyzed using reliability test, factor analysis test, ANOVA and regression test. After spreading the questionnaire for a month, the data is analyzed. The result of the data analysis is brand recognition does not influence brand image, perceived risk and word of mouth does not influence purchase intention. The rest of the hypothesis is correct and shows significant influence. The core variable, Purchase Intention is influenced by Brand Image, Brand as Self, and Brand Loyalty Behavior with the level of each significance are 0.05, 0.009 and 0.009 Keywords: Supercar, Brand Community, Purchase Intention, Brand Image, Brand Loyalty Behavior